Prioritizing the Effective Factors on Surface Erosion Using USLE-M Integrated Model and System Dynamic (A Case Study: Sanganeh Research Center, Khorasan Razavi) - S. Esmailian; A. Talebi; M. Esmailian (علوم آب و خاک, 2018)
This research was aimed to simulate and prioritize the effective factors on water erosion using USLE-M in the system dynamic model. In this integrated model, by using the system dynamic simulation software (Vensim), all variables and factors involved in erosion and soil loss were considered according to the USLE-M model. After model implementation, the estimated values and observations were compared and then sensitivity analysis was done to determine the sensitive parameters. Then, calibration was performed on the sensitive parameters. This study found that that the results of the model were acceptable for soil erosion simulation due to considering all the effective factors in soil erosion. The results of the sensitivity analysis also indicated high model sensitivity to the slope and vegetation cover in high and low slopes, respectively. By investigating the changes in various parameters such as vegetation cover and slope on erosion, the optimal vegetation cover with 67 and 40% slope, was estimated to be 20 and 60%, respectively.